Antithrombotic and hemocompatible properties of nanostructured coatings assembled from block copolymers - Fontelo, R. (2022)
We describe the antithrombotic properties of nanopatterned coatings created by self-assembly of poly(styrene-block-2-vinylpyridine) (PS-b-P2VP) with different molecular weights. By changing the assembly conditions, we obtained nanopatterns that differ by their morphology (size and shape of the nanopattern) and chemistry. The surface exposition of P2VP block allowed quaternization, i.e. introduction of positive surface charge and following electrostatic deposition of heparin. Proteins (albumin and fibrinogen) adsorption, platelet adhesion and activation, cytocompatibility, and reendothelization capacity of the coatings were assessed and discussed in a function of the nanopattern morphology and chemistry. We found that quaternization results in excellent antithrombotic and hemocompatible properties comparable to heparinization by hampering the fibrinogen adhesion and platelet activation. In the case of quaternization, this effect depends on the size of the polymer blocks, while all heparinized patterns had similar performance showing that heparin surface coverage of 40 % is enough to improve substantially the hemocompatibility.